2000
DOI: 10.1016/s0167-4889(00)00045-8
|View full text |Cite
|
Sign up to set email alerts
|

Store-operated Ca2+ inflow in Reuber hepatoma cells is inhibited by voltage-operated Ca2+ channel antagonists and, in contrast to freshly isolated hepatocytes, does not require a pertussis toxin-sensitive trimeric GTP-binding protein

Abstract: The treatment of H4-IIE cells (an immortalised liver cell line derived from the Reuber rat hepatoma) with thapsigargin, 2, 5-di-(tert-butyl)-1,4-benzohydroquinone, cyclopiazonic acid, or pretreatment with EGTA, stimulated Ca(2+) inflow (assayed using intracellular fluo-3 and a Ca(2+) add-back protocol). No stimulation of Mn(2+) inflow by thapsigargin was detected. Thapsigargin-stimulated Ca(2+) inflow was inhibited by Gd(3+) (maximal inhibition at 2 microM Gd(3+)), the imidazole derivative SK&F 96365, and by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…[7][8][9][10] Moreover, other studies with H4-IIE cells have shown that Ca 2ϩ inflow through SOCs (measured using the fluorescent Ca 2ϩ sensor, fura-2) is almost completely inhibited by 2 mol/L Gd 3ϩ or 100 mol/L W7. 25 Taken together with the present results, which show that I SOC in H4-IIE cells can be completely inhibited by 2 mol/L La 3ϩ or 150 mol/L W7, these observations suggest that the Ca 2ϩ -specific SOCs characterized here play a major role in replenishing the Ca 2ϩ that is lost from intracellular stores during hormone-induced Ca 2ϩ signaling in H4-IIE cells. Because a current similar to I SOC has also been observed in rat hepatocytes (Rychkov G, Brereton HM, Barritt GJ, unpublished results, April, 2000), it is likely that rat hepatocytes also possess Ca 2ϩ -specific SOCs (CRAC-like channels) that replenish Ca 2ϩ lost from the endoplasmic reticulum during the generation of hormone-induced Ca 2ϩ signals.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[7][8][9][10] Moreover, other studies with H4-IIE cells have shown that Ca 2ϩ inflow through SOCs (measured using the fluorescent Ca 2ϩ sensor, fura-2) is almost completely inhibited by 2 mol/L Gd 3ϩ or 100 mol/L W7. 25 Taken together with the present results, which show that I SOC in H4-IIE cells can be completely inhibited by 2 mol/L La 3ϩ or 150 mol/L W7, these observations suggest that the Ca 2ϩ -specific SOCs characterized here play a major role in replenishing the Ca 2ϩ that is lost from intracellular stores during hormone-induced Ca 2ϩ signaling in H4-IIE cells. Because a current similar to I SOC has also been observed in rat hepatocytes (Rychkov G, Brereton HM, Barritt GJ, unpublished results, April, 2000), it is likely that rat hepatocytes also possess Ca 2ϩ -specific SOCs (CRAC-like channels) that replenish Ca 2ϩ lost from the endoplasmic reticulum during the generation of hormone-induced Ca 2ϩ signals.…”
Section: Discussionsupporting
confidence: 86%
“…H4-IIE cells (ATCC CRL 1548) were cultured at 37°C in 5% (vol/vol) CO 2 in air in Dulbecco's modified Eagle medium (DMEM) supplemented with penicillin (100 units/mL), streptomycin (100 g/mL), 10 mmol/L HEPES (pH 7.4), and 10% (vol/vol) fetal bovine serum (complete DMEM). [23][24][25] Flasks (25-cm 2 ) were seeded with approximately 0.5 ϫ 10 6 cells. The incubation medium was changed every 2 days, and cultures were confluent in 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…BFA was reported to inhibit CCE in hepatocytes (66), platelets (59), and HEK293 cells (67). But it did not affect CCE in Xenopus oocytes (20) and Reuber hepatoma cells (68). In corneal endothelial cells, treatment with BFA (100 M) for 12 h inhibited CCE in both vehicle-and BN-treated cells (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Nifedipine, verapamil, and diltiazem (inhibitors of L-type calcium channels in excitable cells and store-operated channels at higher concentration in liver cells) (34) did not prevent the toxicity. SKF 96365 (an inhibitor of receptor-operated calcium channels) and benzamil (an inhibitor of Na ϩ /Ca 2ϩ exchange) (34) at 1 and 10 M were also not protective.…”
Section: Effect Of Calcium Channel Blockers On the Toxicity Of Iron Amentioning
confidence: 93%